2011
DOI: 10.1007/s11604-010-0533-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the site of pulmonary embolism and the extent of deep vein thrombosis: evaluation by computed tomography pulmonary angiography and computed tomography venography

Abstract: Proximal PEs were correlated with proximal DVTs. Patients with a proximal DVT tended to have a PE, especially with a right-proximal DVT. Hence, the presence of a right-proximal DVT has the potential for serious complications, and carefully diagnosis is required for PE and DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…We noted a greater proportion of right-sided DVTs among embolized clots, which is consistent with what has been previously reported in the literature for PEs that occur following right-sided versus leftsided DVT. 23,24 The presence of a free-floating tail for thrombi has been also associated in some, 25,26 but not all, 27 previous studies with higher risk of PE; a finding that was also reported in two of the cases in our study. However, the small number of cases found by this systematic review raises caution against firm conclusions.…”
Section: Discussionsupporting
confidence: 79%
“…We noted a greater proportion of right-sided DVTs among embolized clots, which is consistent with what has been previously reported in the literature for PEs that occur following right-sided versus leftsided DVT. 23,24 The presence of a free-floating tail for thrombi has been also associated in some, 25,26 but not all, 27 previous studies with higher risk of PE; a finding that was also reported in two of the cases in our study. However, the small number of cases found by this systematic review raises caution against firm conclusions.…”
Section: Discussionsupporting
confidence: 79%
“…Horii et al15) suggested the use of anticoagulants for proximal DVT and PTE because PTEs were less correlated with distal DVTs in the study. However, prophylactic anticoagulation therapy does not necessarily result in good clinical results.…”
Section: Discussionmentioning
confidence: 78%
“…Anticoagulation therapy was performed in 25 cases, in 17 PTE and 8 proximal DVT15). Of these, 20 cases were available for a second MDCT-indirect venography, which showed complete resolution in 16 cases (80%), ≥50% resolution in 3 cases (15%), and PTE resolution but occurrence of distal DVT in 1 case (5%).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, CTV, which is invasive, has a smaller anatomical blind spot than US, and thus, it can more extensively evaluate venous problems. [ 17 ] However, CTV should be performed in appropriate patients because it is costly and carries a risk of contrast media reaction and post procedural phlebitis. In previous studies, estimates of severe reactions to contrast media such as pulmonary edema, cardiac arrhythmias, and cardiac arrest range from 0.04% to 0.2%.…”
Section: Introductionmentioning
confidence: 99%